Prevalensi ADHD pada Anak di Indonesia: Tinjauan Sistematis Literatur - Nasri, Yosa Yulia; Aldina, Cahya; Mutmainnah, Hafizah; Marlina, Marlina (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Attention Deficit Hyperactivity Disorder (ADHD) is a developmental disorder that affects academic, social, and emotional functioning. In Indonesia, the prevalence rate is significant, yet comprehensive reviews are still limited. The aim is to systematically review the prevalence of ADHD in Indonesia across various age groups and identify factors influencing its diagnosis and management. This study uses a systematic literature review approach. The data sources for this literature review include articles published in scientific journals, totaling 30. Some databases used include Google Scholar, Sage Publications, EBSCO, and repositories of higher education institutions in Indonesia. To ensure the validity and reliability of the findings, every step in this systematic literature review process follows standard guidelines such as PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Qualifying studies were analyzed descriptively. The analysis results show that according to the National Statistics Agency (BPSN) in 2021, about 20% of children and adolescents in Indonesia experience mental health problems, including ADHD, equivalent to 16.8 million individuals. A 2019 study at the Disability Children Foundation of Surakarta (YPAC) reported a prevalence of ADHD of 26.4% among children. Symptoms vary by age, with late diagnosis commonly occurring in adults. Socio-cultural factors, stigma, and limited access to mental health services are major obstacles